FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENYEBAB ANEMIA PADA SANTRIWATI PONDOK PESANTREN DARUL ULUM KABUPATEN KENDAL - Dhenok Citra Panyuluh; Priyadi Nugraha Prabamukti; Emmy Riyanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
The results of Hemoglobin (Hb) examination conducted by the Community Health Nutrition Section of Kendal District Health Office toward teenage girls showed 25.33% (2014), 20.33% (2015), and 25.55% (2016) adolescent girls are suffering from anemia. According to the Ministry of Health, forteenage girls and women anemia is still a public health problem if the prevalence is> 20%. One group of young women who have risk to anemia are female students in a boarding school. The condition of students in boarding school with very dense activities, less of facilities and infrastructure in boarding school, and far from their parents clearly influence the behavior of the students. The purpose of this study is to analyze related factors to the behavior that causes anemia in female students at Darul Ulum Boarding School of  Kendal Regency. This type of research is descriptive with a quantitative approach method in which the population is all female studentsabout 40 people. The samples taken are total sampling. The results showed most respondents have good behavior (70%), most of knowledge about anemia is good (57.5%), most of respondents are supportive to attitudes toward prevention of anemia(52.5%), most of health facilities are not adequate (52.5%), most of health informationsare not adequate (97.5%), family’s attitude and behavior is supportive (75%), peer’s attitude and behavior is supportive (75%), teacher’s attitude and behavior is not supportive (52,5%). There is correlation between teacher’s attitude and behavior with the behavior that causes anemia (p=0,036). It is suggested that there should be education to teachers about health education program in boarding school.